(untitled) (Experimental biology, 2025)
This study examines the distribution and ecological characteristics of Laetiporus sulphureus (Bull.) Murrill in the forest communities of the Ural River valley in the West Kazakhstan region. This fungus, possessing both parasitic and saprotrophic properties, plays a crucial role in the nutrient cycle by decomposing lignin in the wood of deciduous trees. Based on a comprehensive geobotanical and mycological analysis conducted during field studies from 2019 to 2024, it has been determined that L.sulphureus is present across a wide range of forest communities, including elm, willow, poplar, aspen, alder, and oak forests. A strong association between the fungus and tree species such as Quercus robur, Salix alba, and Populus alba has been observed. The results of the study highlight the high ecological plasticity of L. sulphureus, enabling it to effectively adapt to various types of forest communities. ...